ANALISIS DAMPAK (P5) TERHADAP MINAT BERWIRAUSAHA PESERTA DIDIK KELAS XI DI SMA - Betaria, Erika Litia; Ulfah, Maria; Kuswanti, Heni; Asriati, Nuraini; Achmadi, Achmadi (Universitas Tanjungpura, 2025)
The purpose of this study was to determine the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMA Swasta Kapuas Pontianak, students' interest in entrepreneurship and the impact of P5 on students' interest in entrepreneurship. This study used a qualitative approach with a case study method, involving 9 informants consisting of students, principals, vice principals for student affairs and teachers. Data were collected through interview, observation and documentation methods. The results of the study showed that the implementation of P5 activities at SMA Swasta Kapuas Pontianak has been implemented since the first batch in 2022. This P5 activity is carried out every week and has produced various kinds of products. The products produced are still being developed so that they become mandatory entrepreneurial activities for students. Students at SMA Swasta Kapuas Pontianak already have an interest in entrepreneurship. Through P5 activities and existing entrepreneurship, it has a positive impact on students' interest in entrepreneurship. The impact given is that students can have real knowledge and experience of entrepreneurial activities.